THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE, WORK-LIFE BALANCE, WORK ENVIRONMENT WITH EMPLOYEE PERFORMANCE AMONG ACADEMICIANS IN MALAYSIA: AN OVERVIEW - Abdul Rahman, Azura; Esa, Nawal Esa Yazid; Ahmad, Nurul Afiqah; Haron, Hazliza; Sa’adin, Izmayani (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This conceptual paper examines the relationship between Emotional intelligence (EI), work-life balance (WLB) and work environment on employee performance among academicians in Malaysia. The academic profession faces multifaceted challenges, including heavy workloads, research demands, and familial responsibilities, making EI, WLB and work environment vital for their success. This conceptual article examines the relationship between EI, WLB, and performance, synthesizing findings from existing literature and presenting a conceptual framework tailored to Malaysian academicians. Through a review of theoretical and empirical studies, this study synthesizes existing literature to explore how these factors influence performance. By synthesizing insights from existing literature and theoretical frameworks, findings indicate that high EI, effective WLB and work environment significantly enhance employee performance. Recommendations include implementing EI training programs and institutional policies promoting WLB to optimize academic outcomes. This study aims to provide insights for institutions to improve policies and support mechanisms that enhance academic staff performance and well-being.